Latent or Manifest Observers: Two Dichotomous Approaches of Surveillance in Mental Health Nursing - Martin Salzmann-Erikson; Henrik Eriksson (Nursing Research and Practice)
Background. Surveillance is a central activity among mental health nursing, but it is also questioned for its therapeutic value and considered to be custodial. Aim. The aim of this study was to describe how mental health nurses use different approaches to observe patients in relation to the practice of surveillance in psychiatric nursing care. Methods. In this study, Spradley's twelve-step ethnographic method was used. Results. Mental health nurses use their cultural knowing to observe patients in psychiatric care in various ways. Two dichotomous approaches were identified: the latent and the manifest approach. Discussion. Different strategies and techniques for observing patients are structured along two dichotomies. The underlying relationships between these two different dichotomous positions transform the act of observing into surveillance. This is further developed in a theoretical model called the powerful scheme of observation and surveillance (PSOS).